Methylene blue adsorption by langsat peel (Lansium domesticum) waste - Desy Kurniawati; Yona Prestica; Salmariza Sy.; Niza Lian Pernadi (Jurnal Litbang Industri, 2023)
The potential of langsat peel (LP) as an absorbent to remove methylene blue (MB) dye from the textile industry was investigated in this study. A batch method was employed to determine the optimum conditions and adsorption capacity of langsat peel with variations in pH, initial dye concentration, and particle size of the adsorbent. The analysis principle relied on measuring the absorbance of the MB dye before and after adsorption using a Spectronic 20D+ spectrophotometer at a maximum wavelength of 665 nm. The results indicated that the optimum conditions were pH 6, a concentration of 300 ppm, and a particle size of 150 µm. The adsorption process followed the Freundlich isotherm with an R2 value of 0.918 and Kf values of 4.655 mg/g. According to the Langmuir isotherm, the maximum adsorption capacity obtained was 44.843 mg/g.